EFFECT OF LUTEAL REGRESSION ON CONCEPTION RATES IN POSTPARTUM ANESTRUS MURRAH BUFFALOES USING G48 AND G56 OVSYNCH PROTOCOLS - T. Susmita; K. Sunny Praveen; K. Veerabramaiah; P. Veena (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study aimed to investigate the effect of luteal regression on the conception rates in postpartum anestrus graded Murrah buffaloes. Ovsynch protocols: G48 group (n=10) and G56 (n=10) graded Murrah buffaloes, both received a 20 µg dose of GnRH on day 0, followed by 500 µg of PGF2α on day 7. On day 9, a final dose of 20 µg of GnRH was administered 48 hours after PGF2α for G48 and 56 hours after for G56. Fixed-time artificial insemination (FTAI) was conducted at 16-21 hours after 2nd injection in both groups. The luteal regression rates in both the groups were evaluated by progesterone hormone (P4) assay at different days of treatment. The results showed that in both groups, the concentration of P4 differed significantly (P<0.05) between and within groups at different days of treatment. In conclusion, it was found that the G56 group (70.00 per cent) had a higher overall conception rate than the G48 group (50.00 per cent) due to better luteal regression.